GIS-based estimation of catchment basin parameters and maximum discharge calculation using rational method of luinab catchment in Iligan City - dela Rama-Liwanag, Florife; Malales, Vincent; Tudio, Ruben; Sanchez, Kristine; Mostrales, Daniel; Ignacio, Ma. Teresa (2018)
Urban flooding is triggered when surface runoff exceeds the capacity of drainage systems, which happens when heavy rainfall pours on to drainage areas with limited capacity, or on medium rainfall that falls on poorly planned or maintained drainage systems. Due to accelerated population growth and change in land use patterns, human vulnerability to floods has increased, and it is likely to increase further unless changes are made on the urban drainage system. The use of surface runoff and drainage modeling would help to identify- areas that are susceptible to flooding and to determine the dynamic capabilities of urban drainage network. The use of GIS-based software and hydrologic modeling will provide fast and reviewable assessment of the existing drainage system of the catchment. GIS generated results â?? especially in the delineation of catchment and sub-catchments and in identifying drainage networks â?? were validated in the field. Field observations also showed the presence of pollutants and heavy vegetation in the drainage system. Corrected and updated data were then used to calculate of peak discharges using the rational method. The use of rational method in the calculation of the design peak discharges for the catchment resulted in the following values: 21.59, 29.07, 33.82, and 40.31 m3/s for return periods of 2-yr, 5-yr, 10-yr, and 25-yr respectively. The main canal towards the outlet of the catchment is calculated to have a maximum capacity of 7.35 m3/s. This is only 35% of the peak discharge of the storm with a two-year return period. Improvement of the drainage system could be achieved by a) increasing the capacity of main canal and/or b) providing an additional outlet from identified flood-prone areas. The improvement could be further analyzed and evaluated in succeeding hydrologic studies.